Expression of dual oxidases and secreted cytokines in chronic rhinosinusitis. Issue 5 (21st December 2012) - Cho, Do‐Yeon; Nayak, Jayakar V.; Bravo, Dawn T.; Le, Wei; Nguyen, Alan; Edward, Justin A.; Hwang, Peter H.; Illek, Beate; Fischer, Horst
<x xml:space="preserve">Abstract</x> Background The airway epithelium generates reactive oxygen species (ROS) as a first line of defense. Dual oxidases (DUOX1 and DUOX2) are the H2O2‐producing isoforms of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase family in the airway epithelium. The purpose of this study was to explore the molecular expression, function, and regulation of DUOXs in chronic rhinosinusitis (CRS). Methods Human nasal tissue samples and nasal secretions were collected from 3 groups of patients undergoing sinus surgery (normal, n = 7; CRS with polyposis [CRSwP], n = 6; CRS without polyposis [CRSsP], n = 6). Nasal secretions were studied for cytokine and H2O2 content. Tissue samples were used to determine DUOX mRNA and protein expression. Results DUOX1 mRNA level (80.7 ± 60.5) was significantly increased in CRSwP compared to normal (2.7 ± 1.2) and CRSsP (2.3 ± 0.5, p = 0.042). DUOX2 mRNA levels were increased in both CRSwP (18.6 ± 9.9) and CRSsP (4.0 ± 1.3) compared to normal (1.1 ± 0.3; p = 0.008). DUOX protein was found in the apical portion of the nasal epithelium and protein expression was increased in CRSwP and CRSsP. H2O2 production was significantly higher in CRSwP (160.9 ± 59.4 nM) and CRSsP (81.7 ± 5.6 nM) compared to normal (53.5 ± 11.5 nM, p = 0.032). H2O2 content of nasal secretions correlated tightly with DUOX expression (p < 0.001). Cytokines (eotaxin, monokine‐induced by interferon γ [MIG], tumor necrosis factor [TNF]‐α, interleukin [IL]‐8) showed significantly higher levels in nasal secretions from CRSwP compared to normal (p < 0.05). Levels of eotaxin, MIG, and TNF‐α correlated closely with DUOX expression. Conclusion DUOX1 and DUOX2 were identified as factors upregulated in CRS. Close correlations between DUOX expression and H2O2 release, and correlation between key inflammatory cytokines and DUOX expression, indicate DUOX in the inflammatory response in CRS.